(untitled) (De Musica, 2024)
The composer constantly makes choices: it is the composer, in fact, who chooses a melodic, rhythmic, harmonic path among the various, infinite possible paths between point A, the beginning, and point B, the end of a composition. The choice of one path over another, a local modification of a given path, can also be influenced by external factors. As it happens for the path of a charged particle in a magnetic field, the choice of the musical path can be influenced by personal style, culture, technical characteristics of the instruments, and combinations of instruments used. Even in quantum mechanics, there are “choices”: the state of a system appears as a superposition of possible eigenstates with different probability amplitudes. The act of measurement “forces” the system to choose a particular state: the observer influences the physics of the system. Like the famous example of Schrödinger’s cat, alive and dead at the same time until the box in which it is located is opened. From the choices of notes and musical paths to decision-making systems, we present some examples of the application of quantum mechanics to music. Among the applications of quantum computing, we mention a study on robots with associated musical descriptions. In particular, we consider the distributed intelligence of a swarm of robots and its possible musical description, from some existing works to our original application.